Sharia Compliance Risk in Islamic Bank: Does Indonesia Need to Adopt New Sharia Risk Rating Approach - Romi Adetio Setiawan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
The purpose of this study is to find the most relevant practice of supervision to manage Sharia Compliance Risk in Indonesian Islamic Bank based on the existing literature. The standard doctrinal approach is used to analyse, examine and evaluate the practice of Islamic banking supervision in Indonesia and Islamic banking in Malaysia for comparative purposes. The results revealed that the prior study on Sharia risk rating is applicable to manage Sharia Compliance Risk in Islamic Banks and their factors meet the Basel, AAOOIFI, and IFSB standards. However, there is no assessment made on evaluating the quality of supervision by Sharia Supervisory Board (SSB) members. Thus the study suggested the inclusion of additional factors on the performance of SSB. For Islamic Banking in Indonesia, this sharia risk rating approach can be combined with applicable internal and external risk rating techniques, to provide the promising quality of service and ensure that the offering of various products and services complies with Sharia rules and principles.